Developing relationships as a security factor in supply chain management in the metal sector in Poland - Staniewska Ewa (2023)
Ensuring security in the current environment, becomes particularly important in both social and economic terms. The changing conditions for business operators are not conducive to ensuring process stability and thus reducing risks in supply chains. It is becoming essential to identify areas, resources and activities that have the potential to ensure process stability and security and reduce uncertainty as well as risk in supply chains. Developing bonds between business partners is particularly important in this regard. Cooperation based on trust ids the basis of such partnerships in supply chains. At the same time, creating such relationships is not only a challenge, but also an additional source of risk. The objective of this paper is to identify the key aspects of relationship formation within companies and their role in ensuring the security of supply chains. Achieving the purpose of the thesis requires the identification of the essence of relationships and relational capital, and the presentation of research findings on key aspects of corporate relationships in supply chains. The research was conducted using a proprietary questionnaire and covered businesses operating in in the metal industry in Poland. The issues examined included such elements as: competences of enterprises in supply chain management in terms of shaping relations: within the enterprise, with customers, suppliers of materials and services, intermediaries (distributors), the number of contractors with whom enterprises cooperate and the level of their relationships, at which they cooperate, involvement of partners/contractors in decision-making, concepts used in relationships with co-operators, type of contracts and partnerships created, measurement/evaluation of cooperation and the scope of control of cooperation with contractors, elements of building trust, factors conducive to cooperation, barriers and reasons for failures in establishing supply chain management relationships. The research thesis is: identifying the relationships of enterprises with contractors has a positive impact on their formation and ensuring the security of supply chains. The research niche presented in the article concerns the use of opinion and judgment research based on the author's survey questionnaire in the environment of enterprises from the metal industry. Obtaining the results allowed to identify the role and scope of business relationships in supply chains and important factors influencing their shaping. The role of managing relationships with business partners as an important element impacting the security of supply chains was also emphasised.